FAKTOR RISIKO KEJADIAN STUNTING ANAK USIA 1-2 TAHUN DI DAERAH ROB KOTA PEKALONGAN - Tyas Setiyo Yuniarti; Ani Margawati; Nuryanto Nuryanto (JURNAL RISET GIZI, 2019)
Background :Stunting is a short stature caused by chronic malnutrition. Stunting is a result of poor nutrition intake or recurrent infectious disease as area Pekalongan which experienced tidal flooding.Objective: The aimed of this study is to analyze the risk factors for stunting.Methods :An observasional study with case control design on children aged 1-2 years at tidal areaNorth Pekalongan sub district. Sample was selected by method consecutive sampling with 37 subjects for each group. Stunting are expressed by high for age z-score. Subject and respondent identity, history of infection, birth weight, birth length, history of exclusively breastfed, hygiene status, mothers’ knowledge about nutrition and economic status was collected using questionnaire. Nutrient intake were obtained from Semi Quantitative Food Frequency Questionnaire (SQ-FFQ). Children height was measured using microtoise. Bivariate analyzed with chi-square for determining odds ratio and multivariate with multiple logistic regression.Result:Risk factor for stunted were protein intake (OR=3,42, 95%CI:1,31-8,90), iron intake (OR=3,08, 95%CI:1,11-8,50), diarrhea (OR=13,33, 95%CI:3,47-51,22), acute respiratory tract infection (OR=7,01, 95%CI:2,06-23,81), history of exclusively breastfed (OR=19,50, 95%CI:5,56-68,36), hygiene status (OR=4,92, 95%CI:1,83-13,1), dan economic status (OR=4,79, 95%CI:1,21-18,9).Conclusion : Protein intake, iron, diarrhea, upper respiratory tract infection, history of exclusively breastfed, hygiene status and economic status are risk factor of stunting among children aged 1-2 years in tidal area subdistrict North Pekalongan.